Versorgungszustand von Patienten vor Zuweisung an ein universitäres Wundzentrum - Erfurt-Berge, Cornelia; Michler, Melanie; Renner, Regina (Hautarzt, 2021)
Background and objectives: Health care for patients with chronic wounds is often protracted. This can result in decreased quality of care or delayed diagnosis of the actual cause of disease. Concurrently, there are already certified facilities for these patients. The present work investigates possible reasons for delayed referral and whether a specific selection of patients is sent to these university-based centres. Patients and methods: A retrospective patient data chart review at the point of first admission to the certified wound centre was performed to identify concerning variables about the standard of care before university presentation. Results: Records of 177 patients were analysed (53% women, 47% men; patient age range 27–95 years). The mean duration of the wound was 22 months. Vascular diagnostics had already been performed in 32% (arterial diagnostics) and 36% (phlebological diagnostics), respectively. A tissue sample had been analysed in 9% of cases, especially when wound duration exceeded > 24 months. In only 45% of cases was the external diagnosis in accord with the final diagnosis in the wound centre. Discussion: The health care situation for patients with chronic wounds outside of specialised care structures is insufficient. Early and standardized diagnostics and therapy and a reasonable admission to specialised centres is desired.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Basic diagnostics; Care structure; Leg ulcer; Primary care; Quality of care